Psychological Approach to Islamic Studies - Hidayah, Nuril; Faizah, Nur; Mahfudloh, Ririn Inayatul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
The integration of psychological approaches in Islamic studies has gained significant attention in recent years, emphasizing the understanding of human behavior, mental processes, and emotions through both scientific and Islamic perspectives. This paper explores how Islamic teachings, particularly from the Quran and Hadith, align with modern psychological principles, offering a comprehensive framework for mental health, personal development, and emotional well-being. The application of concepts such as nafs (self/soul), fitrah (innate nature), and ruh (spirit) are discussed in relation to psychological theories of personality, motivation, and mental health. By bridging these fields, the study seeks to demonstrate how psychological tools and therapeutic techniques can be adapted within an Islamic framework to enhance spiritual and mental well-being, addressing issues like anxiety, depression, and personal growth. This interdisciplinary approach not only enhances the relevance of Islamic teachings in contemporary mental health discussions but also offers new perspectives for understanding human nature through a spiritual and scientific lens.